Assessment of Anti-Inflammatory Properties of Methanolic Root Extract of Plumeria alba Linn.: An in vitro and in vivo Approach - Nagaraj, Harshitha; Cyriac, Kusu Susan; Jha, Deepak Kumar (International Journal of Pharmaceutical Investigation, 2025)
Background Inflammation is the body's innate defence mechanism that is initiated in reaction to injury or on exposure to detrimental agents. Plumeria alba Linn, a small laticiferous tree rich in phytochemicals and antioxidants is traditionally used to handle a variety of ailments, including ulcers, rheumatism, bronchitis. Objectives and Methodology The purpose of the study was to investigate the anti-inflammatory potential of Plumeria alba methanolic root extract. Following their collection, authentication, and extraction, the roots were evaluated using a variety of in vitro and in vivo experimental models, including HRBC membrane stabilization, heat-induced paw edema, proteinase inhibitor assay, inhibition of albumin denaturation, paw edema, and cotton pellet granuloma respectively. Pro-inflammatory cytokines IL-6 and TNF-α as well as antioxidants SOD, LPO were biochemically analysed. Histopathological examinations of the thigh region of rats were performed to assess structural alterations in the tissue. Results The results revealed thatPlumeria alba significantly reduced the paw edema and granuloma comparable to positive control group. Both the doses of the extract (250 and 500 mg/kg) demonstrated a reduction in pro-inflammatory cytokines, indicating its potential to treat inflammation. Biochemical analyses of antioxidants SOD and LPO showed improvements as well. In vitro analyses showed the extracts have stabilized HRBC membrane, and have anti-haemolytic, anti-proteinase and anti-albumin denaturation properties. Histological assessments revealed that Plumeria alba at 500 mg/kg preserved the structural architecture of the thigh tissue showing reappearance of blood supply and reduced granuloma when compared to the control group. Conclusion The study concludes that Plumeria alba root extract exhibits promising anti-inflammatory properties, likely attributed to its improvement of pro-inflammatory cytokines and antioxidants. These effects suggest that the extract could be used to treat inflammation.
Keywords: Plumeria alba; Carrageenan; Cotton pellet; Granuloma; Paw edema; Tumor Necrosis Factor; Herbal Medicine